2016
DOI: 10.1111/geb.12471
|View full text |Cite
|
Sign up to set email alerts
|

Species and functional diversity accumulate differently in mammals

Abstract: Aim Whether the gradients of global diversity conform to equilibrium or non‐equilibrium dynamics remains an unresolved question in ecology and evolution. Here, we evaluate four prominent hypotheses which invoke either equilibrium (more individuals, niche diversity) or non‐equilibrium dynamics (diversification rate, evolutionary time) to explain species richness and functional diversity of mammals worldwide. Location Global. Methods We combine structural equation modelling with simulations to examine whether sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
145
2
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(158 citation statements)
references
References 85 publications
8
145
2
3
Order By: Relevance
“…According to Oliveira et al (2016) we would expect that the old colonized areas had the highest phylogenetic diversity (Nearctic zone in our study area), nonetheless, our results are congruent with expecta- Table 2. Slope of abiotic variables related with richness (S), phylogenetic diversity (PD) and functional diversity (FD), taking in account for S and PD effects.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…According to Oliveira et al (2016) we would expect that the old colonized areas had the highest phylogenetic diversity (Nearctic zone in our study area), nonetheless, our results are congruent with expecta- Table 2. Slope of abiotic variables related with richness (S), phylogenetic diversity (PD) and functional diversity (FD), taking in account for S and PD effects.…”
Section: Discussionsupporting
confidence: 86%
“…In a global study, Oliveira et al (2016) found evidence showing that mammal species richness and functional diversity are decoupled in America, with species richness being explained by environmental factors (equilibrium processes), whilst functional diversity is related to evolutionary time (non-equilibrium processes). Our results agree with these findings, and also with the general pattern of species richness increase towards the tropics (Rosenzweig 1995, Brown 2014.…”
Section: Discussionmentioning
confidence: 99%
“…Climatic data were taken from the WorldClim database of Hijmans, Cameron, Parra, Jones, and Jarvis () and resampled to the resolution of our distributional maps (1° × 1°), using bilinear interpolation. We selected mean annual temperature (BIO1) and annual precipitation (BIO12) for our analyses because they seem most relevant to mammalian macroecology and macroevolution (e.g., Buckley et al, ; Oliveira et al, ). In addition, we combined all climatic variables (BIO1–BIO19) into a single composite variable (PC1) using principal component analysis (PCA).…”
Section: Methodsmentioning
confidence: 99%
“…Finally, we calculated multiple measures of regional coexistence. These measures were based on the geographical overlaps between species distributions, capturing the degree of resource sharing and partitioning across the species that coexist within a region (Machac et al, ; Oliveira et al, ; Rabosky, ; Rabosky & Hurlbert, ). Specifically, we calculated geographical overlaps between the distributions of mutually related species (i.e., all species within a given clade) but also distributional overlaps with unrelated species (species outside the clade) and with all mammals (species both within and outside the clade).…”
Section: Methodsmentioning
confidence: 99%
“…This index is derived from the average distance between all pairs of species in an assemblage (the mean phylogenetic distance), which Oliveira et al (2016) showed by simulation to be relatively invariant to species richness. We focus on the net relatedness index (NRI).…”
Section: Phylogenetic Analysismentioning
confidence: 99%